How Alumni UMH Uses a Radio Podcast to Increase Internal and External Engagement - García Giménez, Alejandro; Marín Navarro-Soto, Lázaro; Blaya Salvador, Inmaculada; Niñoles Galvañ, Asunción (ICAReAlumni Conference Proceedings, 2019)
This article shares the experience of Alumni UMH in the production of a radio podcast made by and for members of Alumni UMH that achieve objectives of internal and external engagement, internal and external communication, and receive professional collaboration from Alumni UMH members. The different aspects from the design of the radio podcast and planning the season, the development of a typical radio show, and the outcomes and impact attained are shared.